2007
DOI: 10.1016/j.cell.2007.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Riboside Promotes Sir2 Silencing and Extends Lifespan via Nrk and Urh1/Pnp1/Meu1 Pathways to NAD+

Abstract: Although NAD(+) biosynthesis is required for Sir2 functions and replicative lifespan in yeast, alterations in NAD(+) precursors have been reported to accelerate aging but not to extend lifespan. In eukaryotes, nicotinamide riboside is a newly discovered NAD(+) precursor that is converted to nicotinamide mononucleotide by specific nicotinamide riboside kinases, Nrk1 and Nrk2. In this study, we discovered that exogenous nicotinamide riboside promotes Sir2-dependent repression of recombination, improves gene sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
444
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(456 citation statements)
references
References 67 publications
12
444
0
Order By: Relevance
“…4C). Functional NR salvage has been shown to play important roles in maintaining the replication potential of yeast cells (10,12), and NR can restore the RLS of NAD ϩ biosynthetic mutants (10,12). We therefore examined whether deleting POF1 would affect NR mediated RLS extension.…”
Section: Pof1 Functions As An Nmnat Which Catalyzes the Conversion Omentioning
confidence: 99%
See 2 more Smart Citations
“…4C). Functional NR salvage has been shown to play important roles in maintaining the replication potential of yeast cells (10,12), and NR can restore the RLS of NAD ϩ biosynthetic mutants (10,12). We therefore examined whether deleting POF1 would affect NR mediated RLS extension.…”
Section: Pof1 Functions As An Nmnat Which Catalyzes the Conversion Omentioning
confidence: 99%
“…It has been shown that yeast cells produce NAD ϩ predominantly via the NA/Nam salvage pathway during exponential growth (11). More recently, NR has been shown to be an efficient NAD ϩ precursor that contributes to the NAD ϩ pool and supports NAD ϩ -dependent reactions (9,10). Intact NR salvaging pathway is essential for maintaining NAD ϩ homeostasis and life span (12,13).…”
Section: Pyridine Nucleotides Nadmentioning
confidence: 99%
See 1 more Smart Citation
“…163 SIRT1 is 1 of 7 mammalian sirtuin homologs of Sir2, a molecule that catalyzes nicotinamide adenine dinucleotide-dependent protein deacetylation and increases lifespan in worms and flies. 175 The deacetylase activity of SIRT1 targets intermediates involved in the regulation of mitochondrial oxidative metabolism. Specifically, SIRT1 deacetylates PPAR␥ coactivator 1␣ (PGC-1␣), a critical regulator of mitochondrial oxidative metabolism and the maintenance of glucose, lipid, and energy homeostasis, increasing its transcriptional activity.…”
Section: Resveratrolmentioning
confidence: 99%
“…A second pathway involves the conversion of imported nicotinamide riboside (NR) into NAD 1 via the NR kinase (Nrk1p) (Bieganowski and Brenner 2004). A third, newly identified pathway involves direct conversion of NR into NAM by a set of NR hydrolases and phosphorylases (Belenky et al 2007). In the fourth pathway, NAM produced by sirtuin-mediated protein deacetylation or breakdown of NR is converted into nicotinic acid by the nicotinamidase, Pnc1p (Ghislain et al 2002), and then converted back into NAD 1 by the Preiss-Handler pathway, primarily in the nucleus (Anderson et al 2002;Sandmeier et al 2002).…”
mentioning
confidence: 99%